Record to memory - (dokument) (Iluminace, 1991)
Minutes of an extraordinary meeting held at the V. Department of the Ministry of Information on security in the field of film in 1945 in the presence of the Commissioner of the Provincial Department of Security (ZOB II).
Keywords: nationalised film; Ministry of Information; film and politics